Artistic Concept: Approaches and Directions of its Study in Linguistics. / Concepto artístico: enfoques y direcciones de su estudio en la lingüística. - GENNADIEVNA SHTYRLINA, EKATERINA; VIKTOROVNA KHABIBULLINA, ELENA; MIAO, SUN (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The anthropocentric paradigm of modern linguistic science encourages researchers to solve new problems related to the description of mental units concepts. Moreover, the artistic concept, representing a key unit of the cognitive paradigm of researching an artistic text, had several distinctive features: associative nature, imagery and symbolism, emotiveness, orientation to aesthetic information, dialogically, the variability of semantic content, ability to enrich the meaning, etc. The study of the artistic concept further promoted comprehension of the ideological content of the artistic text, comprehension of the author’s conceptual sphere, and identification of the author’s specific idiostyle. RESUMEN El paradigma antropocéntrico de la ciencia lingüística moderna anima a los investigadores a resolver nuevos problemas relacionados con la descripción de conceptos de unidades mentales. Además, el concepto artístico, que representa una unidad clave del paradigma cognitivo de la investigación de un texto artístico, tenía varios rasgos distintivos: naturaleza asociativa, imaginería y simbolismo, emotividad, orientación a la información estética, dialógicamente, variabilidad del contenido semántico, capacidad de enriquecer el significado, etc. El estudio del concepto artístico promovió aún más la comprensión del contenido ideológico del texto artístico, la comprensión de la esfera conceptual del autor y la identificación del idiostyle específico del autor.